Comparative analysis of intravenous midazolam with nasal spray for conscious sedation in minor oral and maxillofacial surgeries - Ramesh Kunusoth; Gururam Tej; Kranti Kiran Reddy Ealla; Pavan Kumar Kathuroju; Anusha Ayyagari; Aditya Mohan Alwala (Journal of Pharmacy and Bioallied Sciences, 2019)
Aim: The aim of the current study was to evaluate the efficacy of nasal spray midazolam by collating it with conventional intravenous midazolam for conscious sedation in minor oral surgeries. Materials and Methods: Sixty patients were selected randomly and divided into two groups: group A for intranasal midazolam atomized spray (n = 30) and group B for intravenous midazolam (n = 30). Physiological parameters, anxiety score, sedation rating, patient’s cooperation score, and retrograde and anterograde amnesia were recorded for each patient during preoperative, intraoperative, and postoperative period. Final evaluation of safety and efficacy in the nasal and intravenous routes of midazolam drug during minor oral surgery was compared. Results: In this study, both intranasal and intravenous groups showed decrease in systolic blood pressure and diastolic blood pressure intraoperatively but within physiological limits and increase in the average pulse rates in both the groups. The average oxygen saturation levels were maintained to normal range in both the groups. The average respiratory rate decreased in both intranasal and intravenous groups during surgical procedure. The preoperative to postoperative anxiety scores were decreased significantly in the both groups and there was no significant difference in pre- to postoperative anxiety scores between the groups. Conclusion: Both intravenous and intranasal administration of midazolam showed better patient cooperation, satisfaction, and clinical effectiveness. Intranasal midazolam spray is effective in the reduction of subjective stress, reliable anxiolysis while preserving protective reflexes.